Pendekatan Rational Emotif Behaviour Therapy (REBT) Teknik Self Control terhadap Mahasiswa dalam Penggunaan Smartphone - Husrin Konadi; Syarifah Ainy Rambe (CERED Indonesia, 2020)
This study aims to see how much student self-control increases in using smartphones through the Rational Emotive Behavior Therapy (REBT) approach. This study used the PTK (Classroom Action Research) method, using two cycles and in each cycle there were four stages, namely planning, implementing, observing, and reflecting. The sample in this study were 30 students of the PGMI study program at the Takengon State Islamic Institute. The results of this study indicate that there is an increase in self-control in smartphone use that occurs in the pre-cycle, cycle 1 and cycle 2 using the REBT technique. In the very low category presiklus there are 3 people, in cycle 1 there is 1 person and there is no very low category in cycle 2. The low category in the presicycle there were 14 people, in cycle 1 there were 8 people, and cycle 2 there were 1 person, in the medium category, there were 5 people in the presicycle, cycle 1 there were 10 people and cycle 2 there were 12 people. Meanwhile, in the pre-cycle high category there were 4 people, in cycle 1 there were 6 people, and cycle 2 10 people. In the very high category, there were 4 people in the presiklus, 5 people in cycle 1 and cycle 2 there were 7 people. Thus there is an increase in student self-control in smartphone use after being given the Rational Emotive Behavior Therapy (REBT) technique.